2006
DOI: 10.1088/0022-3727/39/19/012
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of insulation characteristics of c-C4F8and N2gas mixtures by the Monte Carlo method

Abstract: The motion of electrons in c-C4F8 and N2 gas mixtures for a pulsed Townsend discharge is simulated by the Monte Carlo method. The effective ionization coefficient, , over the E/N range from 160 to 480 Td is calculated by employing a set of cross sections available in the literature. From the variation curve of with the C4F8 mixture ratio k, the limiting field of the gas mixture at different gas content is determined. The required gas pressure ratios comparable with the insulation property of SF6 and GWP a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…The representative potential alternative gases include fluorinated gases (e.g. CF 3 I [23][24][25][26], c-C 4 F 8 [27][28][29]), perfluoroketones (PFK) (e.g. C5-PFK or CF 3 COCF(CF 3 ) 2 ) [30,31] and perfluoronitriles (PFN) (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The representative potential alternative gases include fluorinated gases (e.g. CF 3 I [23][24][25][26], c-C 4 F 8 [27][28][29]), perfluoroketones (PFK) (e.g. C5-PFK or CF 3 COCF(CF 3 ) 2 ) [30,31] and perfluoronitriles (PFN) (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The gas number density is N = 3.29 × 10 22 m −3 in the pressure of 1 Torr at 20 • C. It is assumed that the electron density is sufficiently small, so the Coulomb interactions between the particles as well as shielding of the field are negligible [17]. The procedure of the Monte Carlo method is described in [15][16][17][18][19][20][21][22][23]25]. Hence, a brief overview of this method is given.…”
Section: The Simulation Methodsmentioning
confidence: 99%
“…Tu et al [10] found that the decomposition of CF 3 I after the breakdown and deposition of solid iodine on the surface of the electrode affect the self-recovery of gas. The insulation performance of c-C 4 F 8 , C 3 F 8 , and C 2 F 6 can reach the level of SF 6 in [11,12]. Notably, the GWP values of these compounds at 8700, 7000, and 9200 are less than the value of SF 6 [13], but also could not be ignored.…”
Section: Introductionmentioning
confidence: 99%